Early protection against foot-and-mouth disease virus in cattle using an inactivated vaccine formulated with Montanide ESSAI IMS D 12802 VG PR adjuvant - Quattrocchi, Valeria (2014)
Foot and mouth disease is an acute disease of cattle with a broad distribution around the world. Due to the fast spread of FMDV infections, control measures must be applied immediately after an outbreak, such as the use of vaccines that induce fast protection. Previously, it was shown that mice vaccinated with FMD inactivated virus (iFMDV) formulated with Montanide™ ESSAI IMS D 12802 VG PR adjuvant (802-iFMDV) were protected when they were challenged 4 and 7 days post-vaccination (dpv) with homologous virus. In this work, we describe the successful use of this formulation in cattle. In addition, adjuvant Montanide™ IMS 1313 VG NPR was also tested. 802-iFMDV vaccine was able to confer 100% protection against viral challenge at 4 and 7 dpv, while eliciting low antibody levels, at 7 dpv. 1313-iFMDV vaccine induced protection in 60% of cattle. At 4 dpv, 1313-iFMDV vaccinated animals presented increased levels of IFNγ but not of macrophages. At 4 and 7 dpv, macrophages, IFNγ, nasal IgA and IgG1 antibodies against FMDV, and opsonophagocytosis were increased in animals vaccinated with 802-iFMDV indicating that these phenomena could be involved in protection.It is the first time that total protection against FMDV at early stages post-vaccination is reported using a single dose of the formulation iFMDV plus Montanide™ ESSAI D IMS 12802 VG PR adjuvant.